Performance Evaluation of three Indian Wheat Varieties Under Iraqi Environment - Al Obaidi, A. J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The performance of the Indian wheat varieties (PBW34, PBW343 and WH542) was compared with the local varieties (Tamose â€“ 2 and Abu Ghareeb).      The experiment was conducted during two seasons first 2000-2001 and second 2001-2002 at AL- Twaitha experimental station , middle of Iraq.         The results showed that (Tamose â€“ 2) exceeded the other varieties in plant height and heading date in the two seasons, while WH542 gave the lowest plant height.  PBW34 variety showed a significant increase in 1000 grain weight followed by PBW343 in the second season. Moreover, PBW34 and PBW343 gave the highest average of 50 spike weight in the second season.  In the two seasons PBW343 exceeded Abu Ghareeb in grain yield and surpassed WH542 in the first season 2000 only. No significant differences were found between PBW343, PBW34 and Tamose â€“ 2 in grain yield.